Alteration of esophageal motility by intraluminal temperature [OZOFAGUS MOTILITESININ LUMEN ICI SICAKLIGI ILE DEGISIMI] - (:unkn) unknown (My University, 1997)
Esophageal motor activity is altered by bolus temperature. The effect of a sustained cold or warm temperature on esophageal motility has not been documented in detail. Esophageal manometry was performed in 11 normal subjects after intraluminal room, cold, and warm temperature water treatments. The intraluminal temperatures were 34.2 ± 0.8, 30.6 ± 1.7 and 39.7 ± 0.9 C respectively after room, cold and warm temperature applications. Cold temperature treatment prolonged the duration of lower esophageal sphincter relaxation and the esophageal peristaltic contraction wave as compared with the room and warm temperature treatments. Cold temperature also decreased the mean pressure slope of esophageal contraction waves and resulted in an increased percentage of nontransmitted and simultaneous contractions. The effects of cold temperature application were persistent as long as the intraluminal temperature remained constant and there was no adaptation. Cooling the intraesophageal lumen alters esophageal motor activity and this effect is not adaptive.
Keywords: Esophagus; Motility; Temperature